2008
DOI: 10.1016/j.anireprosci.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Xenografting of adult mammalian testis tissue

Abstract: Xenografting of testis tissue from immature males from several mammalian species to immunodeficient mouse hosts results in production of fertilization-competent sperm. However, the efficiency of testis tissue xenografting from adult donors has not been critically evaluated. Testis tissue xenografting from sexually mature animals could provide an option to preserve the genetic material from valuable males when semen for cryopreservation cannot be collected. To assess the potential use of this technique for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 19 publications
3
56
1
Order By: Relevance
“…Degeneration of graft testicular tissue could have possibly occurred because of the absence of the natural scrotal environment and exposure to hyperthermic conditions at the ectopic site of grafting. The adult testes of species with high daily sperm production such as pig and goat after xenografting to mice recipients showed a complete degeneration of tubules and grafts (Arregui et al 2008). However in species such as bull and monkeys where daily sperm production is low, xenografted adult testes had either degenerated tubules or …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Degeneration of graft testicular tissue could have possibly occurred because of the absence of the natural scrotal environment and exposure to hyperthermic conditions at the ectopic site of grafting. The adult testes of species with high daily sperm production such as pig and goat after xenografting to mice recipients showed a complete degeneration of tubules and grafts (Arregui et al 2008). However in species such as bull and monkeys where daily sperm production is low, xenografted adult testes had either degenerated tubules or …”
Section: Discussionmentioning
confidence: 99%
“…Survival of only seminiferous tubules with Sertoli cells was seen in mature bull and monkey donor grafts; however, complete spermatogenesis was observed when the donor graft tissue was not completely mature (Arregui et al 2008). No germ cell differentiation was observed in adult human testes xenografted onto mouse hosts (Geens et al 2006.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…36 For still unknown reasons, mature testis tissue grafts do not support germ cell differentiation as well as immature testis tissue grafts in xenograft models. 38 To further demonstrate this finding, Yu and colleagues 39 transplanted fetal (20-26 weeks) human testicular tissue subcutaneously onto an immunodeficient nude mouse and demonstrated that the xenograft could survive for more than 135 days. These fetal grafts did extremely well; with increased graft weight, Sertoli cell differentiation and germ cell migration were demonstrated over time.…”
Section: Testis Xenograft Transplantation Modelmentioning
confidence: 99%